Pengaruh Loyalitas Moral dan Brand Benefit terhadap Loyalitas yang Dimoderasi oleh Brand Association - Andre Ramadhan; Lasmaria Tampubolon; Saskia Saskia (Universitas Harapan Medan, 2021)
This study aims to determine the effect of moral loyalty on product loyalty of Converse shoes, the effect of brand benefits on product loyalty of Converse shoes, to determine whether the brand association moderates the relationship between moral loyalty and product loyalty of Converse shoes and to determine whether the brand association moderates the relationship between brand benefits and product loyalty. Converse shoes. The population in this study were 112 students of the Faculty of Economics, Universitas Harapan Medan who used Converse brand shoes and all of them were sampled in this study. Data analysis used is multiple linear regression and moderated regressions analysis. The results showed that moral loyalty did not have a significant effect on product loyalty from Converse shoes, brand benefits had a positive effect on product loyalty from Converse shoes, brand association moderated the relationship between moral loyalty and brand loyalty Converse shoes, The brand association moderates the relationship between brand benefits and product loyalty for Converse shoes.